2012
DOI: 10.1126/scisignal.2002677
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Imaging of Epithelial Cell Scattering Identifies Specific Inhibitors of Cell Motility and Cell-Cell Dissociation

Abstract: The scattering of cultured epithelial cells in response to hepatocyte growth factor (HGF) is a model system that recapitulates key features of metastatic cell behavior in vitro, including disruption of cell-cell adhesions and induction of cell migration. We have developed image analysis tools to automatically track and characterize this process in live cells without the need for fluorescent tagging, in three different physical aspects: increase in cell motility, loss of cell-cell adhesion, and spatial dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 25 publications
(31 reference statements)
2
28
0
1
Order By: Relevance
“…All cell lines were grown at 37°C in a humidified atmosphere of 5% CO 2 in air. Migration and adhesion assays of MK Itga3 fl/fl and MK Itga3 −/− (6) on a laminin-332 rich matrix deposited by Rac11-P cells were performed as previously described (20,(34)(35)(36). Murine skin cancer cell lines P1, B9, and A5 were cultured as described (23,24) (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…All cell lines were grown at 37°C in a humidified atmosphere of 5% CO 2 in air. Migration and adhesion assays of MK Itga3 fl/fl and MK Itga3 −/− (6) on a laminin-332 rich matrix deposited by Rac11-P cells were performed as previously described (20,(34)(35)(36). Murine skin cancer cell lines P1, B9, and A5 were cultured as described (23,24) (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…1A and provided additional information at the single-cell level. Quantifying the ratio of E-cadherin staining at individual cell-cell junctions relative to junction-proximal regions, as in previous studies related to cell adhesion (Loerke et al, 2012;Č áslavský et al, 2013), demonstrated that the overall decrease in E-cadherin expression observed by western blot was accompanied by a delocalization of E-cadherin from cell-cell junctions in response to TGFβ with or without EGF. Analysis of vimentin staining revealed that the higher total levels of vimentin expression measured by western blot reflected an increased percentage of vimentinpositive cells.…”
Section: Egf Augments Tgfβ-induced Emtmentioning
confidence: 99%
“…Weakening cell-cell junctions within preformed epithelial cell clusters can lead to disrupted cluster circularity and scatter of cells away from these clusters (Loerke et al, 2012). These changes can be monitored by measuring a cluster circularity index, calculated as 4π(area/perimeter 2 ), which has a value of 1 for a circle or 0 for a line (Č áslavský et al, 2013).…”
Section: Egf Augments Tgfβ-induced Emtmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several techniques developed, including segmentation of invading cells and calculation of scattered tumor area [16], calculation of nearest-neighbor distance measures between cells [10], and cellular motility [7]. As in our current work, we will develop several features that will measure different aspects of cell spread, and use these features to identify which feature is most altered in +HGF spheroids vs. controls.…”
Section: Discussionmentioning
confidence: 99%